POLITIK LUAR NEGERI INDONESIA PADA MASA PEMERINTAHAN PRESIDEN JOKO WIDODO MELALUI PENGUATAN DIPLOMASI EKONOMI - Mariane Olivia Delanova (Universitas Jenderal Ahmad Yani, 2017)
After President Joko Widodo won in general electoral in 2014, he has making many decisions, include decision on foreign policy. One of his priorites of foreign policy is on economic sector. President has been implementing Indonesia’s foreign policy, which is improving economic diplomacy to achieve national interests of Indonesia, especially in the era of free trade and globalization. This paper aims at analyzing Indonesia’s foreign policy in the era of President Joko Widodo, focus on economic diplomacy of Indonesia, and include the change on paradigm of Ministry of foreign affairs. This paper also tries to describe the obstacles in practicing foreign policy of Indonesia in the era of President Joko Widodo.